Is the Technology Acceptance Model Valid for Entrepreneurs? Model Testing and Examining Usage Determinants - Nelson Oly Ndubisi; Muhamad Jantan; Stanley Richardson (Asian Academy of Management Journal, 2001)
IT researchers regard Technology Acceptance model (TAM) as a powerful model for understanding technology acceptance in general. Manay have claimed it is the most popular model of technology acceptance, having been used in many studies involving different user groups. But very often overlooked is the test of TAM on entrepreneurs, a distinct and important group which researchers have found to exhibit unique traits. Because of these peculiar traits, this research believes that a separate TAM study on entrepreneurs is warranted. TAM theorizes that perceived usefulness directly influences usage and perceived case of use directly and indirectly via usefulness influences usage. This research investigates the validity of the TAM among Malaysian contrepreneurs. This is because fast developing economy. The study found that IT usage was influenced directly by perceived usefulness and indirectly (via usefulness) by perceived case of use. Contrary to TAM's postulation, there is no direct relationship between perceived case of use and usage. Details of the research findings and their implications are dicussed.